FAKTOR-FAKTOR PENYEBAB KURANGNYA MINAT MEMBACA BUKU PAKET PAI DAN SOLUSINYA PADA PESERTA DIDIK KELAS X IPS DI SMAN PALLANGGA - Kasrawati; Halimah, Andi; Hamsiah Djafar; Rafiqah (Al asma : Journal of Islamic Education, 2022)
The ability to read requires habituation. The presence of high reading interest can encourage individuals to more easily absorb concepts from their reading materials. This research was conducted with the intention to find out the factors that cause the lack of interest in reading, especially in PAI package books and the solution for students of class X IPS at SMAN 1 Pallangga. This research is a type of qualitative research. The source of this research data is class X IPS students and PAI teachers. The data collection methods used are questionnaires, interviews, observations, and documentation. Data processing and analysis techniques are carried out through three stages, namely: data reduction, data presentation, and conclusion drawing. The results of this study showed a variety of factors that cause the lack of interest in reading class X IPS learners at SMAN 1 Pallangga, namely: lack of awareness of students about the importance of reading, lack of motivation from parents, lack of role of PAI teachers in assigning tasks to learners, poor arrangement of libraries, lack of variety of PAI package books in libraries. The solution carried out by PAI teachers from the factors that cause the lack of interest in reading PAI package books is the need for the authorship and motivation of the students’ parents by inviting them when receiving a report card every semester and briefing him on his child's achievements in school to be further improved, and the arrangement of the library at SMAN 1 Pallangga must be improved so that students are interested in visiting and reading books in the library.